Participación estudiantil en el proceso de aseguramiento de la calidad de la carrera de Enfermería de la Universidad Estatal de Bolivar en el periodo 2018-2019 - Aucatoma Cautullin, Gonzalo Fabricio (2019)
The theme "STUDENT PARTICIPATION IN THE PROCESS OF ASSURING THE QUALITY OF THE NURSING CAREER OF THE STATE UNIVERSITY OF BOLIVAR IN THE PERIOD 2018-2019" arises with the purpose of promoting student participation for the fulfillment of one of the indicators of the Council of Quality Assurance of Higher Education (CACES). The main objective of this work is to encourage student participation in the Career Quality Assurance process. This type of research is indispensable since it was possible to demonstrate the lack of interest on the part of the students as well as the little knowledge about criteria and sub-criteria, since 78% of the students state that they do not know about the Evaluation of the Learning Environment and their results in the Nursing Career of the State University of Bolívar that was carried out by the Council for the Evaluation, Accreditation and Quality Assurance of Higher Education, Taking into account the bibliographical research and the results obtained from the questionnaire applied to students, it is recommended to the authorities to hold seminars in which they can report the progress and results that are obtained in the Quality Assurance of the Nursing Career. The present investigation reaches a depth level of descriptive type since it allows to clearly understand the information gathered in the theoretical framework and the results obtained from the data collection, helping the description of characteristics of student participation in the assurance process of The Quality of the Nursing Career of the State University of Bolívar. Keywords: Student participation, indicators, criteria, subcriteria, career evaluation.